Academic performance indicator as performance management tool: employees' perception and factors governing to its acceptance and rejection in Indian educational institutes. (5th January 2022) - Luthra, Anchal; Singh, Kavita; Singh, Shweta
Academic performance indicator is a topic of great discussion among the academicians of Indian educational institutes. UGC implemented the API score to upgrade the quality of education and research in India. However, teachers have different opinions about API. Therefore, this paper aims to study the opinion of academicians working in different private and public institutes and to explore the factors that are contributing towards its acceptance and rejection, particularly by a third category, i.e., research category. The study was mainly qualitative, but the percentage method was also used as a quantitative tool to analyse the data. Results claimed that the maximum percentages of teachers despite working on different hierarchical levels were in favour of implementation of API as it motivates to acquire more knowledge. However, there were also teachers who felt that it should not be there as it is purely a mechanical experience which reduces innovation and creativity in research.